The acute time course of muscle and tendon tissue changes following one minute of static stretching - Andreas Konrad; Markus Tilp (Bern Open Publishing, 2020)
The purpose of this study was to investigate the time course of the changes of various muscle and tendon mechanical properties and the function responses of the plantar flexor muscles following 1 min of static stretching. Twenty-five healthy volunteers were assigned into a static stretching group or a control group. The static stretching group was tested with three different rest times (0 min,20 min,40 min) after 2x30s of stretching. Controls were tested before and after a control period (10 min) without stretching. Dorsiflexion range of motion (RoM), passive resistive torque (PRT), and maximum voluntary contraction (MVC) were measured with a dynamometer. Ultrasonography of the medial gastrocnemius (GM) muscle-tendon junction (MTJ) displacement allowed us to determine the length changes in the tendon and muscle, respectively, and hence to calculate their stiffness. Following the stretching, we observed a significant increase in RoM directly following the stretching, 20 min post-stretching, and 40 min post-stretching. However, no changes were found in other functional parameters (PRT, MVC) or structural parameters (muscle and tendon stiffness). No changes were detected in any variable in the control group. We conclude that a static stretching exercise of 2x30s increases the RoM for at least 40 min. However, this gain in RoM is not accompanied with more compliant muscle and/or tendon tissue, suggesting that 60s of static stretching might not be stimulus enough to induce changes in the muscle-tendon structure. Hence, we speculate that other factors, such as increased stretch tolerance, might be responsible for the changes in the RoM observed in the present study.